It’s the incentives, stupid! - Longva, Leif; Smedsrød, Bård (Septentrio Conference Series, 2023)
Watch VIDEO.From 2004, a new incentives system for scholarly publishing was introduced in Norway. Part of the funding of the HE institutions has since been based on the amount of scholarly publishing produced per institution, as recorded in the Norwegian CRIS system, Cristin. And the incentives worked. Publishing increased more rapidly in Norway than in comparable countries, over the years following 2004 (Aagard et al. 2014).But the sheer number of journal articles, anthologies and monographs is not necessarily what best brings science forward. And now the Norwegian government has announced that the publishing count will be dropped from the funding scheme (Meld. St. 14). Thus, we suggest that the right move would be to instead direct the incentives to stimulate good, transparent open science research practice.The advantages of open science, both for further research advancement and the benefit to society, are well documented (Miedema 2022). This includes early and obstacle-free access to research output in terms of articles, peer review reports and commentaries, as well as access to the research processes with preregistration and registered reports, methods and protocols, as well as FAIR research data that enables reproducible research.So, what is needed is an incentive system that stimulates such research practices. We suggest an incentive system, through the funding schemes of the institutions. This should favour institutions that follow open science practices. The institutions will thus be incentivized to stimulate open science, and identify and remove possible bottlenecks in their organisations that may hamper execution of open science. As employers of researchers as well as support staff, the managers of the institutions will look for ways to optimize local incentives, and also how their organisation may be designed, to best live up to the ideals of open science practices.Based on the above, we suggest a systematic evaluation of each HE institution, to document how well they practice such openness in their research. To accomplish this a list of criteria that can be easily monitored and objectively evaluated is needed. Several of the open research output parameters should be easy to monitor and measure through a reporting system. The evaluation should also acknowledge that necessary limitations to open processes and outputs exists, and thus avoid biases between institutions due to the nature of their research.Incentives directed towards the institutional level to stimulate open research practices will motivate the management to stimulate their organisation in the desired direction.
Keywords: Open Science; Incentives